Educating Aerobic Exercise and Skill-Related Fitness of Athletes in University of Ilorin - Bakinde, Surajudeen Tosho (Indonesian Journal of Multidiciplinary Research, 2022)
Fitness is regarded as having sound strength and endurance, which promotes a healthy mind. Exercise is repetitive bodily movements done to improve or maintain one or more of the components of fitness. Skill-related health concepts are the underlying skills that are needed in sports competition includes body balance, speed, agility, power, coordination, and reaction time. This study examined the influence of aerobic exercise on the physical related fitness of athletes in the University of Ilorin. The factors investigated are muscular power, agility, body balance, speed of athletes in the University of Ilorin. A descriptive research design of survey type was used for the study. The population of the study was 150 athletes in the University of Ilorin. The purposive sampling technique was used to select the entire 150 registered population by questionnaire. Frequency and percentage were used to analyze the demographic data of respondents and the four null hypotheses were tested using the inferential statistic of chi-square at 0.05 alpha level. The findings revealed that; aerobic exercise has a significant effect on the muscular power, agility, body balance, and speed of athletes in the University of Ilorin. Based on the findings, the study recommends that University of Ilorin athletes should engage in power explosive exercise with the help of the coaches to improve their muscular power, Athletes in the University of Ilorin should engage their players in the Illinois Agility run test to determine their agility level and engage in agility exercise to maintain and improve their agility fitness level.